Health Commodity Security Project - World Bank (World Bank, 2010)
Information document about the Health Commodity Security Project. It is divided in the sections below: - Country and Sector Background - Objectives - Rationale for Bank Involvement - Description - Financing - Implementation - Sustainability - Lessons Learned from Past Operations in the Country/Sector - Safeguard Policies (including public consultation) - List of Factual Technical Documents - Contact point - For more information contact
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; health / saúde

Astill-Brown_Weimer_Moz_conflict_por.pdf - Astill-Brown, Jeremy; Weimer, Markus (Chatham House, 2010)
Este documento foi comissionado pelo Departamento de Desenvolvimento Internacional do Reino Unido (DfID) com o objectivo de ajudar a desenvolver, em todo o governo britânico, uma melhor compreensão dos desafios à paz e à segurança em Moçambique. O documento foi concebido principalmente para contribuir para o desenvolvimento da política do governo britânico (e correspondente estratégia de influência) em relação a Moçambique, bem como para aprofundar a consciência dos riscos potenciais inerentes às abordagens adoptadas pelo governo britânico para a prestação de assistência no sector de desenvolvimento. Embora o documento se baseie, em grande parte, na Análise Estratégica de Conflitos de 2006 – e embora muitas das suas conclusões sejam semelhantes – a verdade é que tem um âmbito muito mais extenso. O documento contém uma análise de vários aspectos do conflito embora conste, de uma maneira geral, de uma análise de riscos políticos focalizando um ambiente político e económico variável. Como tal, cobre assuntos de interesse para a comunidade governamental britânica em geral, propondo ainda sinergias entre esta e o programa de desenvolvimento. O documento cobre apenas as principais questões estratégicas e proporciona um ponto de partida para discussões intra-governamentais sobre linhas de acção que sejam tanto possíveis como apropriadas. Esta investigação teve início em Fevereiro de 2010, com um período de revisão da literatura. A seguir, em Março do mesmo ano, os autores visitaram Moçambique, onde entrevistaram doadores, funcionários do governo, membros de partidos políticos e de organizações da sociedade civil, académicos e outros interessados, à procura não de dados mas sim de impressões e perspectivas. As suas conclusões preliminares foram apresentadas em Maputo, em Maio de 2010. As investigações foram lideradas por Jeremy Astill-Brown e Markus Weimer, com a ajuda de Carolina Hunguana e Alex Vines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; security / segurança

Ex-Post Evaluation Report of Grant Aid Projects 2009 (Mozambique) - JICA (Japan International Cooperation Agency (JICA), 2010)
Ex-post evaluation of ODA projects has been in place since 1975 and since then the coverage of evaluation has expanded. Japan’s ODA charter revised in 2003 shows Japan’s commitment to ODA evaluation, clearly stating under the section “Enhancement of Evaluation” that in order to measure, analyze and objectively evaluate the outcome of ODA, third-party evaluations conducted by experts will be enhanced. This volume shows the results of the ex-post evaluation of Grant Aid projects that were mainly completed in fiscal year 2006. The ex-post evaluation was entrusted to external evaluators to ensure objective analysis of the projects’ effects and to draw lessons and recommendations to be utilized in similar projects.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Final Report 1 of 3 Summary - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part I-II - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-IV - JICA (Japan International Cooperation Agency (JICA), 2010)
The Study Road (N13: Cuamba – Mandimba – Lichinga), as part of the two Mozambican corridors (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors), provides a strategic link to the Malawi Border at Mandimba with the ports of Nacala and Pemba, in Nampula and Cabo Delgado Provinces respectively. Although the Study Road has much potential for stimulating development and reducing poverty throughout the entire northern area of Mozambique by enabling efficient connection, the section concerned is the only unpaved section. The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-V - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors)
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part VI: Environmental and Social Considerations - JICA (Japan International Cooperation Agency (JICA), 2010)
In response to the request from the Government of the Republic of Mozambique, the Government of Japan decided to conduct the Preparatory Survey on Road Improvement Plan in Nacala Development Corridor (N13: Cuamba-Mandimba-Lichinga) and entrusted the study to the Japan International Cooperation Agency (JICA). Objectives of the study: (1) The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. (2) Formulation and recommendation of the “Regional Development Program” intended for Niassa Province is also the objective of the Study.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part IV Economic Feasibility Study - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter1 Existing Traffic Flow Patterns This chapter aims to analyze traffic flow patterns on the Study Road based on various information in order to conduct the appropriate traffic demand forecast. Chapter 2 International Goods Transportation Though Nacala Corridor This chapter aims to discuss the current condition of international goods transportation through Nacala Corridor in order to estimate future traffic demand on the Study Road. Chapter 3 Traffic Demand Forecast 3.1 Macro-Economic Background 3.2 Forecasting Methods 3.3 Traffic Demand Forecast 3.4 Results of Traffic Forecast Chapter 4 Economic and Financial Analysis (Cuamba-Mandimba Section) The Study objective is “to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing earth/ gravel roads in the rural areas to paved roads.” For the purpose of the economic evaluation, it is important to first define the existing state of the Project road for the base case, and then to define the alternatives to be analyzed, and finally the structure of the analysis.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part V Cross-Border Facilities - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter 1 Mozambique-Malawi Border Control and Facilities 1.1 Current Condition of Cross-Border Traffic between Mozambique and Malawi 1.2 Border Facilities between Mozambique and Malawi 1.3 Border Control System and Border Facilities Chapter 2 Mandimba Border Control and Facilities 2.1 Characteristics of Mandimba Border Area 2.2 Cross-Border Traffic and Cargo 2.3 Mandimba Border Post and Facilities 2.4 Chiponde Border Post and Facilities Chapter 3 Strategy for Upgrading Border Control and Facilities 3.1 SADC-COMESA Regional Strategy 3.2 One Stop Border Posts 3.3 Mozambique-Malawi Bilateral Strategy Chapter 4 Implementation Approach for Upgrading Mandimba Border Facilities 4.1 Needs Assessment and Proposed Approach for Implementation 4.2 Methodology for OSBP Phased Introduction 4.3 Challenges to OSBP Introduction Chapter 5 Border Development Strategy for Upgrading Mandimba Border Facilities 5.1 Traffic Demand Forecast at Mandimba-Chiponde Border 5.2 Proposed Implementation Policy 5.3 Proposed Facility Planning for Phased Introduction of OSBP
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Small and Medium Enterprises (smes) Access to Finance in Selected East Asian Economies - Harvie, Charles; Oum, Sothea; Narjoko, Dionisius A (ERIA - Economic Research Institute for ASEAN and East Asia, 2010)
Findings from ERIA’s SME research project in FY 2009 confirms that access to finance is amongst the most critical factors determining the competitive readiness of regional SMEs and their ability to fully exploit and participate in the global economy and business opportunities from regional economic integration and, in particular, participation in regional production networks. Well recognized in the literature, access to funding is the lifeblood of any enterprise, enabling it to grow, and to generate more output and employment. There is considerable evidence to support the contention that SMEs, in particular, face a number of obstacles and problems in accessing finance, mainly related to their limited resources and perceived risk by lenders. This is particularly problematic and worrisome for policy makers, given that SMEs and entrepreneurship are widely recognized as being the key sources of dynamism, innovation, and flexibility in advanced industrialized, emerging market and developing economies, and are major net job creators in these economies. Without access to finance, SMEs are unable to invest, impairing their capacity to: improve productivity; raise competitiveness; promote innovation; generate employment; and contribute to economic growth and development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; ⛔ No DOI found

The Expansion of Tree Monocultures in Mozambique. Impacts on Local Peasant Communities in the Province of Niassa - Overbeek, Winfridus (Movimento Mundial pelas Florestas Tropicais, 2010)
This publication is the result of a visit to Mozambique in November 2009 by two activists involved in the struggle against tree monocultures in the Brazilian state of Espírito Santo. This visit was made possible by the World Rainforest Movement (WRM) with the goal of exchanging experiences about large-scale tree monocultures. With more than 40 years of dealing with monoculture plantations and expansion, Brazil has a lot of experience in this area. At the same time, affected communities and supporting organizations in the country have led several struggles and acts of resistance and formed alliances, which nearly ten years ago resulted in the foundation of the Alert against the Green Desert Network (Rede Alerta contra o Deserto Verde). In the past few years, WRM has been made aware of the fact that more and more tree monocultures are being planted in Mozambique. Since Brazil and Mozambique have in common Portuguese as their official language, the idea arose to promote the exchange between the two countries so as to: − exchange experiences with the affected communities about the impacts; − better understand the current situation of the introduction and expansion of tree monocultures in Mozambique; and, − identify organizations involved or interested in the subject. This visit would not have been possible without the invaluable help of our friends at UNAC (União Nacional de Camponeses - National Peasant Union) in Mozambique, and UCA (União dos Camponeses e Associações de Lichinga - Union of Peasant and Associations of Lichinga), who volunteered to receive and accompany the Brazilian delegation and organized the visits to the communities. We also want to thank Via Campesina Brasil for their support in this initiative.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural

Gender and poverty in Mozambique - Tvedten, Inge (CMI Brief, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

Género e pobreza em Moçambique - Tvedten, Inge (CMI, 2010)
A igualdade de género e o empoderamento das mulheres estão no centro das agendas do governo e dos doadores na África Sub-Sahariana, mas no geral não conseguiram ter impacto. Mais do que a ‘integração’ do género, é necessária mais atenção às variações da posição das mulheres. Numa série de três estudos sobre políticas de género e feminização da pobreza em Moçambique, foram encontradas diferenças significativas entre o norte e o sul, bem como entre as áreas rural e urbana. É essencial que se compreendam estas variações para se desenhar políticas e intervenções relevantes para a melhoria das condições das mulheres no país.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; empowerment / empoderamento; gender / género; poverty / pobreza

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

'Não fica bem que uma mulher seja chefe quando existem homens'. Género e Pobreza no Sul de Mocambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2010)
Este relatório final é o terceiro da série "Políticas de Género e Feminização da...
Keywords: G - Mozambique / Moçambique; G - south / sul; L - portuguese / português

The politics of poverty: Elites, citizens, and states - findings from ten years of DFID-funded research on governance and fragile states 2001-1010 - UK DFID Research and Evidence Staff (UK Department for International Development (DFID), 2010)
This research adds depth to our understanding of development as a political process, provides rich evidence based on country experience, and points to the questions which aid agencies must address in order to be effective – including in more fragile countries. It demonstrates that durable reforms need to be constructed, nationally and locally, in a way that fits each political context and it challenges donors to build the capacity to contribute to this effectively
Keywords: *indexed; *tagged; L - english / inglês; citizenship & participation / cidadania e participação; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; decentralization / descentralização; fragility / fragilidade; governance / governação; poverty / pobreza; taxation / tributação